PENGARUH CYBER SECURITY STRATEGY AMERIKA SERIKAT MENGHADAPI ANCAMAN CYBER WARFARE - Saputera, Moehammad Yuliansyah; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes United States of America’s Cyber Security Strategy facing the cyber warfare threads from 2009 till 2014. The main goals are securing cyber vital infrastructures and digital informations of United States. Vital infrastructures are composed of public and private institutions in the sectors of agriculture, food, water, public health, emergency services, government, defense industrial base, information and telecommunications, energy, transportation, banking and finance, chemicals and hazardous materials, postal and shipping, internet network, and many others.The method that is used in this research is qualitative research. Some of the datas are obtained from books, journals, articles, internet and other media. This research focuses on the influence of United State’s cyber security strategy facing cyber warfare threads. Using strategy theory and securitization theory, this research will find out if US government successes to secure their cyber environment or not.Cyber warfare is a thread, it can be a trigger to the physical war. Cyber attackers can compromise other computers or networks to use as intermediaries, or channel through anonymizing proxies that hide their Internet protocol (IP) address. Also, using underground internet or deep web can penetrate enemy’s database. Through the intelligence agencies, United States applied it. It has multy functions. Can be a tool for defense or securing cyberspace and also can be a tool to attack.Keywords: Cyber Security Strategy, Cyber Warfare, Deep Web